Large-Scale Investigation of Soybean Gene Functions by Overexpressing a Full-Length Soybean cDNA Library in Arabidopsis - Li, Xiang; Huang, Lei; Lu, Jianhua; Cheng, Yihui; You, Qingbo; Wang, Lijun; Song, Xuejiao; Zhou, Xinan; Jiao, Yongqing (Frontiers in Plant Science, 2018)
Molecular breeding has become an important approach for crop improvement, and a prerequisite for molecular breeding is elucidation of the functions of genetic loci or genes. Soybean is one of the most important food and oil crops worldwide. However, due to the difficulty of genetic transformation in soybean, studies of its functional genomics lag far behind those of other crops such as rice, which severely impairs the progress of molecular improvement in soybean. Here, we describe an effective large-scale strategy to investigate the functions of soybean genes via overexpression of a full-length soybean cDNA library in Arabidopsis. The overexpression vector pJL12 was modified for use in the construction of a normalized full-length cDNA library. The constructed cDNA library showed good quality; repetitive clones represented approximately 4%, insertion fragments were approximately 2.2 kb, and the full-length rate was approximately 98%. This cDNA library was then overexpressed in Arabidopsis, and approximately 2000 transgenic lines were preliminarily obtained. Phenotypic analyses of the positive T1 transgenic plants showed that more than 5% of the T1 transgenic lines displayed abnormal developmental phenotypes, and approximately 1% of the transgenic lines exhibited potentially favorable traits. We randomly amplified 4 genes with obvious phenotypes (enlarged seeds, yellowish leaves, more branches, and dense siliques) and repeated the transgenic analyses in Arabidopsis. Subsequent phenotypic observation demonstrated that these phenotypes were indeed due to the overexpression of soybean genes. We believe our strategy represents an effective large-scale approach to investigate the functions of soybean genes and further reveal genes favorable for molecular improvement in soybean.